The Effect of Inflation, Interest Rate and Rupiah Exchange Rate on JCI in Food and Beverage Manufacturing Companies Registered on The Indonesian Stock Exchange (IDX) - Refera Bella Safitri (Majalah Ilmiah Bijak, 2021)
This study aims to determine the effect of inflation, interest rates, and the exchange rate of the rupiah against the JCI in manufacturing companies in the food and beverage sector on the Indonesia Stock Exchange. This research uses quantitative methods. Data collection techniques are carried out by processing data that has been published by Bank Indonesia, BPS. Data processing and analysis techniques used include descriptive statistical analysis, multiple linear regression, classical assumption test, correlation coefficient analysis, multiple correlation coefficient analysis, and hypothesis testing. The results showed that inflation has a negative and significant effect on the JCI. This result can be proven by the value of tcount <ttable (-2.265190 <-1.993) and a significance value of <(Î±) (0.0265 <0.05) so that H11 is accepted. Interest rate variable has no effect on the JCI. This result can be proven by the value of tcount <ttable (1.801611 <1.993) and a significance value> (Î±) (0.0758> 0.05) so that H02 is rejected. The Rupiah Exchange Rate variable has a positive and significant effect on the JCI. This result can be proven by the value of tcount> ttable (3.520699> 1.993) and a significance value <(Î±) (0.0008 <0.05) so that H13 is accepted. The coefficient of determination shows that the Adjusted R-squared is 0.282205. This means that the ability of the independent variable in explaining the variation of the dependent variable is 28.22%, while 71.78% is explained by other variables that are not included or explained in this study. 993) and the significance value> (Î±) (0.0758> 0.05) so that H02 is rejected. The Rupiah Exchange Rate variable has a positive and significant effect on the JCI. This result can be proven by the value of tcount> ttable (3.520699> 1.993) and a significance value <(Î±) (0.0008 <0.05) so that H13 is accepted. The coefficient of determination shows that the Adjusted R-squared is 0.282205. This means that the ability of the independent variable in explaining the variation of the dependent variable is 28.22%, while 71.78% is explained by other variables that are not included or explained in this study. 993) and the significance value> (Î±) (0.0758> 0.05) so that H02 is rejected. The Rupiah Exchange Rate variable has a positive and significant effect on the JCI. This result can be proven by the value of tcount> ttable (3.520699> 1.993) and a significance value <(Î±) (0.0008 <0.05) so that H13 is accepted. The coefficient of determination shows that the Adjusted R-squared is 0.282205. This means that the ability of the independent variable in explaining the variation of the dependent variable is 28.22%, while 71.78% is explained by other variables that are not included or explained in this study. 993) and a significance value <(Î±) (0.0008 <0.05) so that H13 is accepted. The coefficient of determination shows that the Adjusted R-squared is 0.282205. This means that the ability of the independent variable in explaining the variation of the dependent variable is 28.22%, while 71.78% is explained by other variables that are not included or explained in this study. 993) and the significance value <(Î±) (0.0008 <0.05) so that H13 is accepted. The coefficient of determination shows that the Adjusted R-squared is 0.282205. This means that the ability of the independent variable in explaining the variation of the dependent variable is 28.22%, while 71.78% is explained by other variables that are not included or explained in this study.